(Des)conexões na educação para a saúde integral : um estudo de caso com catadores de uma cooperativa - Behs, Izar Müller (2014)
The current research is characterized by an investigative approach a case study that is part of the research line Person and Education of the Post-Graduation Program in Education of Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS). Aiming to understand the conditions of the garbage collectors work in a sorting cooperative of inorganic garbage, located in Canoas City, in the Rio Grande do Sul State, and its relation to the integral health education, the subjects of the study were observed and interviewed. The study followed the principle of triangulation of evidences, data were collected through a participant observation, as well as individual semi-structured interviews were recorded in a field diary, and a social economic questionnaire, and a focus group session were applied. In order to organize and analyze data, two strategies were used: the first, that is more restrict and has a quantitative feature, aimed the statistical organization of data, which were collected through social and economic questionnaire; and the second, whose objectives are broader, is particularly qualitative, and the content analysis was used accordingly to Bardin (2008). Decomposition, structuring, and interweaving of the collected material enable the expression, idea and statement grouping, that were classified in meaning units, so that four categories emerged in the current study: 1) identity and occupation: focusing on the garbage collectors conception related to their identity and occupation; 2) work environment: in which many words were grouped, related to coping the risk and the occupational diseases, as well as to the presentation of the reflections associated to the way they face risks and also the feelings of pain and pleasure in the work environment; 3) representation of integral health: the ideas that garbage collectors create about mental and body structures, as well as diseases and their treatments; 4) health education and diversity of spaces: they are related to the garbage collectors experiences that trigger learning opportunities, preventive orientation and care, considering integral health perspective. The results showed that education for integral health has to be treated from different perspectives, that can be science, through many subjects; common sense; from objective and subjective views; and in individual and collective approach. Regarding to education, the focus is on how to value the knowledge of the other person, comprehending that knowledge is a process of collective construction and, taking into account health, when it is analyzed in a broader sense body and soul its basis is on the understanding of human beings fundamental, material and spiritual needs. Health education, considered as socially produced and associated to a set of values, requires a coordinated action, in combination with intervention methodologies, which are related to different social groups. The valorization of education can produce a new perspective to the garbage collectors, to their production and their own lives. Thus, education for life should integrate the person s solidary and integrality ethic.